BIMBINGAN SISWA SD MENJADI TERANG DAN GARAM DI SEKOLAH HIDUP DALAM NILAI-NILAI KRISTIANI - Afari Sarumaha (Universitas Nias Raya, 2025)
Counseling guidance in Elementary Schools plays a crucial role in shaping students' character based on Christian values. One of the main goals of counseling is to help students become the